Economic Analysis of High-Density Apple Plantation Scheme in Jammu and Kashmir - Hassan, Bakhtaver; Bhattacharjee, Mahua; Wani, Shabir A (Asian Journal of Agriculture and Rural Development, 2020)
This paper evaluates the performance of the high-density apple plantation scheme, launched in 2016 in Jammu & Kashmir, India to boost both productivity and production of apples, amidst the stagnancy witnessed in the sector. Primary data was collected from apple farmers in two districts, Kulgam and Pulwama. The qualitative techniques were used to estimate the yield, establishment cost, and break-even year of the different orchard densities. Multiple Regression Analysis and multivariate statistical techniques were used for yield-forecasting and estimation of Net Present Value and Internal Rate of Return respectively. The results show that the yield has increased by two-five times than the traditional orchards. Break-even year for different densities without government was found to be 6-years while with government support it went down to just 4-5 years. Net Present Value and Internal Rate of Return, further substantiate high-profitability and early returns in these orchards. Further, it was concluded that the government subsidy provides significant support to the farmers in two main densities - 2200trees/hectare and 3300trees/hectare. Thus, the government should broaden the scheme and make it more inclusive for the overall development of the sector.